Romatolojide Güncel Kılavuzlar - Karadeniz, Hazan; Küçük, Hamit; Güzelant Özköse, Gül; Çimen Güneş, Ezgi; Tecer, Duygu; Bilici, Reyhan; Ermurat, Selime; Fırlatan, Büşra; Kılıç, Levent; Avanoğlu Güler, Aslıhan; İçaçan, Ozan Cemal and Ergülü Eşmen, Serpil and İnce, Burak and Kart Bayram, Gözde Sevgi and Kılıç, Levent and Bektaş, Murat and Tezcan, Dilek and Ocak, Tuğba and Coşkun, Belkıs Nihan and Akyol, Lütfi and Gücenmez, Sercan and Yılmaz, Zevcet and Sunkak, Saliha and Yıldızgören, Mustafa Turgut and Ünal Enginar, Ayşe and Akar, Zeynel Abidin (Academician Publishing Book DOI Portal, 2023)
-